Measurement of jet substructure observables in t t events from proton-proton collisions at s =13 TeV measurement of jet substructure observables - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
A measurement of jet substructure observables is presented using t¯t events in the lepton þ jets channel from proton-proton collisions at ffiffi s p ¼ 13 TeV recorded by the CMS experiment at the LHC, corresponding to an integrated luminosity of 35.9 fb−1. Multiple jet substructure observables are measured for jets identified as bottom, light-quark, and gluon jets, as well as for inclusive jets (no flavor information). The results are unfolded to the particle level and compared to next-to-leading-order predictions from POWHEG interfaced with the parton shower generators PYTHIA 8 and HERWIG 7, as well as from SHERPA 2 and DIRE 2. A value of the strong coupling at the Z boson mass, αSðmZÞ ¼ 0.115þ0.015 −0.013 , is extracted from the substructure data at leading-order plus leading-log accuracy